Autoimmune Diseases and Molecular Mimicry in Tuberculosis - Leonid P. Churilov; Muslimbek G. Normatov; Hong Ling; Min Zhuang; Dmitry Kudlay; Anna Starshinova (Biology)
Comorbidities in tuberculosis patients are increasing annually. Autoimmune pathology may influence the diagnosis and treatment of tuberculosis (TB). However, the molecular mimicry between Mycobacterium tuberculosis (Mtb) and human autoantigens is an important provocative factor in the development of autoimmunity on one hand. Mtb has already been widely discussed as a provocateur of autoimmunity in humans. The aim of this study was to determine whether molecular mimicry exists between Mtb antigens and human autoantigens previously demonstrated as targets of autoimmunity. Materials and Methods: We analyzed the level of antibodies in 19 patients with pulmonary tuberculosis. In all cases ELISA assays was used. Also, in parallel, we identified 29 similar pentapeptides between key Mtb antigens and human autoantigens. Bioinformatic methods were used in this study. All amino acid sequences of MT antigens and human autoantigens were obtained from the UniProt database, and similar epitopes between Mtb antigens and human autoantigens were identified using the original “Alignmentaj” program. The immunoreactivity of the shared pentapeptides in Mtb antigens was evaluated with use of the IEDB database. Results: The high level of antibodies to modified citrulinated vimentin (anti-MCV) was most frequently detected (57%) in comparison with other antibodies. Elevated levels of antibodies to C3 complement fragments (47%) and rheumatoid factors (21%) in the absence of any rheumatic or autoimmune diseases are noteworthy. Several of the shared pentapeptides belong to the immunoreactive epitopes of Mtb antigens. The bioinformatic data correlated with our earlier studies of the levels of corresponding autoantibodies in the sera of TB patients. Conclusion: Our findings on cross-reactivity and sequence similarity between the Mtb proteins and human autoantigens provide support for the role of antigen mimicry in TB-related autoimmunity.